Georgia - Li, Richard Ruochen; Kitchen, Hannah; George, Bert; Richardson, Mary; Fordham, Elizabeth; Organisation for Economic Co-operation and Development (OECD reviews of evaluation and assessment in education, ISSN 2223-0947, 2019)
Summary.
Keywords: koulutus : Georgia; opetus : Georgia; opettajat : Georgia; koulutuspolitiikka : Georgia; koulutusjärjestelmät : Georgia; koulutus : arviointi : Georgia